(untitled) (Global Scientific Review, 2023)
In this work, 4 different tTt, tGg’, gTg’ and gGg` conformations of the ethylene glycol (EG) molecule were studied using quantum chemical calculations and the method of B3LYP//6-311++G(d, p). Using the calculation, the optical and geometric parameters of the conformations were determined, and at the same time, the change in the shape of the O-H vibration band was analyzed in the conformations.